A Human Factors Perspective on Ethical Concerns of Vehicle Automation. (September 2016) - Kumfer, Wesley J.; Levulis, Samuel J.; Olson, Megan D.; Burgess, Richard A.
This paper presents a knowledge synthesis of ethical questions for the application of rational ethics theories to human factors in vehicle automation. First, a brief summary of ethical concerns related to transportation automation and human factors is presented. A series of theoretical questions are then posed for different levels of vehicle automation. Particular concerns relating to the Principle of Utility and the Principle of Respect for Persons are highlighted for low levels of automation, high levels of automation, and full automation through the use of theoretical scenarios. Although some recommendations are drawn from these scenarios, the primary purpose of this paper is to serve as a starting point to encourage discussion and collaboration between human factors professionals, engineers, policymakers, transportation officials, software programmers, manufacturers, and the driving public regarding realistic goals for automated vehicle implementation.